Mafhūmu kalimātu “Qawlan Ma’rūfan dan Qawlan Sadīdan” fi Sūrati An-Nisā’ (Dirosah Ad-dalālah Al-qur’āniyah) - Mahmud Rifaannudin; Arina Sabilahaq (Jurnal Ulunnuha, 2021)
The miracle of al-qurān in terms of language, al-qurān is the source of knowledge in this modern era. And al-qurān written in Arabic which contains meaning and science, including nahwu, ṣorof, dalālah and Balāghoh. Insaid I'lmu dalālah discusses about Ṣifah wal Mauṣūf, because the sentence is imperfect meaning if there are no words that characterize it. One sentence will be discussed in word of "Qawlan" which is characterized by word of Ma’rūfan and Sadīdan. Seeing the meaning of two sentences that are the same good words, but each has a different purpose and that is by looking at the terms of meaning according to language and time of use is also intended for the intended. Finaly, the first  of resulted: that the phrase "Qawlan Ma'rūfan" has a meaning of a good expression, also this expression show up to orphans when giving wealth to those who have reached the age and also, can be used when talking to close friends, and to him poor people when giving some treasure. And the second is: the meaning of "Qawlan Sadīdan" has a meaning of a kind expression which is gentle and just shown to ṣufaha. and ṣufaha has two meanings, the first: Little boys and the second: girls. pronounced when giving a will or inheritance to the Sufaha.